Socio-Psychological Factors of a Personal Decision on Labor Migration (Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Psihologìâ, 2020)
The article deals with the problem of decision-making by an individual on labor migration. There was studied directly the phenomenon of labor migration, its features in the global and Ukrainian scale. The modality of influence on the development of the economy and public life of Ukraine is considered. There were outlined social and psychological factors influencing decision making. Among the factors, the crisis life situations of a person are highlighted, namely, an age crisis, a spiritual crisis, a biographical crisis. We also describe the life strategies by which a person is guided in his life. Such an important factor as the nervousness of the situation in which a person is found is considered. The levels of his stress resistance. The phenomenon of "decision" and the necessary conditions for its adoption are analyzed. There was theoretically substantiated the study of the effectiveness dependence in the decision-making process on social indicators and psychological criteria of the personality. The sample in the study consisted of 44 women who are citizens of Ukraine, 22 women of whom have work experience abroad, and the other half is considering this option and is in the process of forming and making an appropriate decision. As a result of empirical research, certain parameters of dependence were found by socio-psychological factors in decision-making. Considering the psychological aspect, there was found a relationship between the prevailing coping strategy that a person chooses to act in stressful situations and the general indicator of resilience - on the one hand, and the ability to make decisions - on the other. The result of our research is a developed program that helps women in overcoming internal obstacles on the way to improving the quality of their own life, because the ability to make decisions indicates the awareness of oneself as a subject of their own life about sufficient resilience.